(3QSGdI aj YOe fSHI GdTQ Edi Gddgs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CMSf Ndb eUfhY agPg QSGdI eYehdI ai HjGf SQ YOe fSHI GdTQEdi Gddg JYGdi Cf QShd Gddg cGf jbhd ai OYGA GdGSJaJGM dHjc hSYOjc hGdNjQ ai jOjc hGdTQ djS Edjc s
(3BNQgG (B:s
(3aGf GdWHjH GdMGPb bO jSJYed GdSe ai ERGdI GdeQV adg CjVkG hLg eYbhd GdG Ef eG bOefGg COb hHGdbHhd CMb Je s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B31s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3GdJhMjO hGdedd hGdfMds